Intensive feeding alters the rumen microbiota and its fermentation parameters in natural grazing yaks - He, Shichun; Yuan, Zaimei; Dai, Sifan; Wang, Zibei; Zhao, Shusheng; Wang, Rongjiao; Li, Qing; Mao, Huaming; Wu, Dongwang (Frontiers in Veterinary Science, 2024)
Amidst the challenging environmental conditions characterized by low oxygen levels and cold temperatures on the plateau, alterations in nutrient supply emerge as pivotal factors influencing the survival and reproduction of yaks. Intensive feeding stands out as a substantial mechanism for nutrient provision, initiating discernible changes in the host's rumen flora. Within the extreme natural conditions prevailing in the plateau area of northwest Yunnan, China, there exists a con-strained comprehension of the variations in rumen microflora, fermentation parameters, and growth responses exhibited by yaks subjected to intensive feeding. This study employs 16S rRNA and ITS sequencing methods to scrutinize the rumen flora of yaks engaged in both natural grazing (G)and intensive feeding(F)on the plateau. The outcomes unveil that, during the severe winter season, yaks adeptly modulate the abundance and diversity of rumen flora in response to dietary modifications under intensive feeding, aiming to optimize the efficient utilization of dietary fiber and energy. Principal Coordinate Analysis (PCoA) illustrates a substantial alteration in the rumen microbial community of naturally grazing yaks when exposed to intensive feeding. The natural grazing group manifests a higher prevalence of Firmicutes and Bacteroidetes, while the intensive feeding group exhibits heightened levels of Prevotella in the rumen. The Rikenellaceae _ RC9 _ gut_ group, associated with mycobacteria, prevails more abundantly in the natural grazing setting. PICRUSt2 analysis indicates that intensive feeding induces bacterial gene overexpression linked to protein metabolism. Rumen fungi showcase heightened diversity under intensification. Intensive feeding results in an augmented abundance of non-fiber-degrading bacteria and semi-fiber-degrading bacteria, accompanied by elevated concentrations of Volatile Fatty Acids (VFA). These findings yield novel insights into the shifts in the rumen microflora of yaks acclimated to intensive feeding in high-altitude environments, provide an important reference for the nutritional regulation of supplemental feeding of natural grazing yaks in the cold season, ultimately contributing to their enhanced growth.